Global attitudes on and the status of enteral nutrition therapy for pediatric inflammatory bowel disease - Luo, Juan; Xie, Yong-Mei; Wu, Mei; Zhao, Jin-Gui; Hu, Liang-Liang (Frontiers in Medicine, 2022)
Enteral nutrition (EN) is a diet-remission therapy for inflammatory bowel disease (IBD) that plays a more important role in children than adults. EN includes exclusive enteral nutrition (EEN), partial enteral nutrition (PEN), and maintenance enteral nutrition (MEN). However, EEN remains an unstandardized treatment for pediatric IBD. The types and methods of EN differ around the world. The current study reviewed the EN literature on IBD children. Twelve survey studies were identified that analyzed the current state of EN use, including clinical opinions, implementation methods, treatment course, EEN formula, IBD classification, progress, dietary reintroduction, and patient feedback. The findings revealed that EEN has a strong effect on mild to moderate Crohn's disease (CD). The usage rates of this treatment in different sites were ileum/colon (Paris classification L3) > ileum (L1) > upper digestive tract (L4) > colon (L2) > perianal disease (P) > ulcerative colitis (UC) > extraintestinal lesions. Polymeric formula was the most used EN formulation. New EN diets include a CD exclusion diet (CDED), a specific carbohydrate diet (SCD), and a CD treatment-with-eating (CD-TREAT) diet. Children with IBD responded similarly to EEN administered orally or using a feeding tube. Most guidelines recommended 6–8 weeks of EEN treatment to induce remission. Many clinicians preferred to combine drug medications during EEN and recommended that MEN account for at least 25–35% of daily caloric intake. EN remains an unstandardized therapy that requires teamwork across disciplines.